Catalyst for preparing olefin by dehydrogenation of low-carbon alkane
By preparing a catalyst using millimeter-sized sulfur-containing alumina microspheres with high crushing strength and suitable bulk density as a support, the problems of complex catalyst preparation and insufficient activity in the prior art have been solved, and a highly efficient dehydrogenation reaction of low-carbon alkanes to olefins has been achieved.
Patent Information
- Application Number
- CN202410861233.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-12-30
AI Technical Summary
In existing catalytic dehydrogenation processes for producing olefins from low-carbon alkanes, the catalyst preparation process is complex, the catalyst activity and selectivity are low, and the resistance to coking is insufficient, making it difficult to meet the requirements of moving bed processes.
Using millimeter-sized sulfur-containing alumina microspheres as a carrier, alumina sol was prepared through a specific process and then dropped into an oil-ammonia column for molding. Combined with the loading of specific active components, a catalyst with high crushing strength, suitable bulk density and aspect ratio was prepared, eliminating the need for a pre-sulfurization step.
It improves the activity and selectivity of the catalyst, reduces the coking rate, meets the requirements of moving bed process, and improves alkane conversion and olefin selectivity.
Smart Images

Figure BDA0004919212850000161 
Figure BDA0004919212850000171 
Figure HDA0004919212860000011
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to catalysts with alumina pellets as carriers, in particular to a catalyst with millimeter-sized sulfur-containing theta-alumina pellets as carriers for dehydrogenation of low-carbon alkanes to olefins. BACKGROUND
[0002] Catalytic dehydrogenation of low-carbon alkanes to the corresponding olefins is an important chemical process. Low-carbon olefins are very important chemical raw materials and have a wide range of applications in the chemical industry. For example, propylene is widely used to produce polypropylene, acetone, acrylonitrile, propylene oxide, acrylic acid, and other chemical products. Isobutylene is the main raw material for producing methyl tert-butyl ether (MTBE). Butene is mainly used in alkylation, polymerization, isomerization, and dimerization processes to synthesize useful gasoline components and fuel additives such as MTBE and ETBE gasoline additives, and is widely used in the field of chemicals. Catalytic dehydrogenation of propane / isobutane is an important source of propylene / isobutene. Currently, the main catalytic dehydrogenation processes for propane / isobutane that have been industrialized include the Oleflex process of UOP using a moving bed, and the Catofin process of ABB Lummus using a fixed bed.
[0003] For moving bed processes, usually 3 or 4 reactors are used, and the catalysts are usually supported platinum-based catalysts with alumina as the carrier, which is modified by adding other components to improve the activity and selectivity of the catalyst. The alumina carrier plays an important role in improving the activity stability of the catalyst and improving the performance of the catalyst.
[0004] The above process for preparing Pt-Sn / θ-Al2O3 catalysts usually involves first preparing alumina pellet carriers, then loading promoters and active components, and finally using different sulfidation processes to reduce the initial activity of the catalyst. The catalyst preparation process is complex, and there is no report on the preparation of sulfur-containing alumina pellets and their performance in alkane dehydrogenation after loading active components.
[0005] Alumina is widely used as catalyst carrier, adsorbent and hydrogenation catalyst in petroleum and chemical industry due to its high specific surface area, narrow particle size distribution, good adsorption, thermal stability and surface acidity. Hydrated alumina powder is peptized under acidic conditions as binder or carrier of catalytic cracking and hydrogenation catalyst. The peptized activated alumina can increase the mechanical strength and pore structure of the catalyst to some extent, and improve the catalytic performance of the catalyst. Shaping is a crucial link in the production and application of industrial catalysts. For different industrial production devices, the catalyst needs to be shaped into different shapes and sizes to meet the needs of continuous production. For the Oleflex process of moving bed propane dehydrogenation to propylene, Pt-Sn / θ-Al2O3 catalyst is used. In order to realize the continuous transportation and regeneration of the catalyst and meet other industrial design requirements, reduce the mechanical wear of the catalyst, the carrier alumina must be made into round pellets with a diameter of 1.4-2.0 mm, and the crushing strength should be not less than 39 N / pellet.
[0006] The method of preparing spherical alumina by aluminum sol hot oil column shaping was first seen in US2620314. US2620314 used aluminum and hydrochloric acid solution to prepare aluminum sol, which was mixed with hexamethylenetetramine solution and then shaped in a hot oil column device. After pressurized aging in an oil bath, water washing, drying, calcination and water vapor pore expansion treatment, spherical alumina was obtained. This method has many procedures, and each procedure takes a long time. The pore distribution of the alumina pellets prepared by this process is dispersed, and the hydrothermal stability is low.
[0007] CN87101513A uses aluminum chloride and ammonia water to carry out neutralization reaction at 60-80℃, and then alumina sol is obtained. The alumina sol is dropped into an oil ammonia column device to shape, dried after aging, and treated by water vapor pore expansion at 600-800℃ to obtain the final product. The impurity content of the alumina sol prepared by inorganic raw material method is high, the length-diameter ratio of the alumina pellets is poor, and the crushing strength is low.
[0008] CN102718241B discloses a method for preparing spherical alumina particles by seaweed acid assisted shaping. The method drops sodium alginate-pseudo-boehmite suspension into an aqueous solution of aluminum, calcium, barium, copper, zinc, manganese or cobalt metal ions, forms gelatinous acid-pseudo-boehmite gel composite pellets, and then obtains spherical alumina particles after water washing, drying and calcination. The obtained alumina pellets have high bulk density and low crushing strength.
[0009] CN105502447A discloses a method for preparing alumina pellets by hot oil column shaping. Urea and water are added to pseudo-boehmite prepared by alkyl aluminum hydrolysis method to form a suspension, which is then peptized with acid. Hexamethylenetetramine is added to the aluminum sol and mixed uniformly, and then dropped into a hot oil column to form pellets. The alumina pellets are directly collected at the bottom end of the hot oil column, and then washed with water, dried and calcined to obtain high-purity alumina pellets.
[0010] The direct catalytic dehydrogenation reaction of low-carbon alkanes is limited by thermodynamic equilibrium, with high temperature and low pressure favoring the reaction. However, excessively high reaction temperatures can increase propane cracking, leading to severe coking and accelerated catalyst deactivation. To improve the catalyst's resistance to coking and extend its lifespan, sulfidation is usually required to reduce its initial activity and slow down the deactivation rate.
[0011] CN102463152A discloses a method for processing a dehydrogenation catalyst, wherein the catalyst is Pt, Sn, K, or a rare earth metal supported on an alumina support. The catalyst is impregnated with a solution containing a sulfiding agent. The sulfiding agent solution is an inorganic polymeric sulfide solution, formed by dissolving elemental sulfur in K₂S, Na₂S, or (NH₄)₂S solution, and the amount of elemental sulfur added to the sulfiding agent is 20-90% of the theoretical sulfur required for the dehydrogenation catalyst.
[0012] CN102463148A discloses a sulfidation start-up method for a dehydrogenation catalyst, employing a platinum group supported dehydrogenation catalyst. The catalyst is typically supported on alumina. After impregnation with a solution containing a sulfiding agent, the catalyst undergoes heat treatment in the presence of steam. The sulfiding agent is elemental sulfur, and an organic carboxylic acid ester is used as a solvent. The amount of elemental sulfur added is 70%–150% of the theoretical sulfur requirement for the dehydrogenation catalyst.
[0013] CN102909012A discloses a method for activating a dehydrogenation catalyst, wherein the catalyst is obtained by supporting Pt, Sn, and K on an alumina support. Before use, the catalyst undergoes a pre-reduction process followed by isothermal reduction. The reduced catalyst is then passivated using a mixed gas containing hydrogen, hydrogen sulfide, and nitrogen, with a molar ratio of hydrogen sulfide, hydrogen, and nitrogen of 1:9:(0–30).
[0014] The above-mentioned process for preparing Pt-Sn / θ-Al2O3 catalysts typically involves first preparing alumina microspheres as supports, then loading additives and active components, and finally using different sulfidation processes to reduce the initial activity of the catalyst. The catalyst preparation process is complex, and when applied to alkane dehydrogenation reactions, the start-up process is complicated. Furthermore, there are no reports on the preparation of sulfur-containing alumina microspheres and their alkane dehydrogenation performance after loading active components.
[0015] In existing technologies for preparing alumina carriers using aluminum sulfate and sodium aluminate as raw materials, due to the high content of impurity elements and low acid-colloidal solubility index, kneading or extrusion molding is generally used. There are no reports of preparing alumina microspheres by drop molding. Summary of the Invention
[0016] The purpose of this invention is to provide a catalyst for the dehydrogenation of low-carbon alkanes to olefins using millimeter-sized sulfur-containing θ-alumina microspheres with special physicochemical properties as a support. This catalyst is used for the dehydrogenation of low-carbon alkanes to olefins and has high activity and selectivity, as well as low coking rate.
[0017] To achieve the above objectives, the present invention provides a catalyst for the dehydrogenation of low-carbon alkane to olefins, comprising an alumina support and an active component, characterized in that the alumina support is a millimeter-sized sulfur-containing θ-alumina microsphere with a particle size of 1.6-2.5 mm and a specific surface area of 80-150 m². 2 The micrometer-sized sulfur-containing θ-alumina microspheres are obtained by the following steps: adding a hydrated alumina suspension to an acid solution to obtain an alumina sol, then dropping it into an oil-ammonia column to form microspheres, drying, and calcining. The hydrated alumina comprises at least two types of hydrated alumina, and at least one of the hydrated alumina is hydrated alumina P2, with an acid solubility index (DI) of 50%-85%. The microspheres have a pore volume of 0.40-0.75 mL / g, a crushing strength greater than 50 N / particle, a bulk density of 0.55-0.80 g / mL, an aspect ratio (b / l) greater than 0.95, and a sulfur content of 0.05%-0.50%.
[0018] The catalyst of this invention uses millimeter-sized sulfur-containing θ-alumina microspheres as a support. These alumina microspheres are prepared by reacting hydrated alumina with acid solutions to form an alumina sol, which is then shaped into microspheres by oil-ammonia column dropping, followed by drying and calcination. They possess unique physicochemical characterization parameters different from existing technologies, exhibiting high crushing strength, high aspect ratio, and suitable bulk density. When used in the dehydrogenation reaction of low-carbon alkanes, this catalyst eliminates the need for catalyst pre-sulfurization during start-up and meets the requirements of moving bed processes. It also demonstrates high alkane conversion and olefin selectivity, and strong resistance to coking. Attached Figure Description
[0019] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with the following detailed description to explain the invention, but do not constitute a limitation on the scope of the invention. In the drawings:
[0020] Figure 1 This is a wide-angle XRD diffraction pattern of the alumina microspheres in Examples 1-3 of this invention (the horizontal axis is the 2θ diffraction angle, and the unit is...). o The vertical axis represents the diffraction intensity.
[0021] Figure 2 In Example 1 of this invention, the dynamic morphology of the alumina microspheres was analyzed using a CamsizerX2 instrument from Lech Corporation. A high-speed camera captured images of the particles in a flowing state, and the average particle size and aspect ratio b / l were statistically calculated. Detailed Implementation
[0022] A catalyst for the dehydrogenation of low-carbon alkanes to olefins comprises an alumina support and an active component, characterized in that the alumina support is a millimeter-sized sulfur-containing θ-alumina microsphere with a particle size of 1.6-2.5 mm and a specific surface area of 80-150 m². 2 / g, pore volume of 0.40-0.75mL / g, crushing strength greater than 50N / particle, bulk density of 0.55-0.80g / mL, aspect ratio b / l value of ≥0.95, and sulfur content of 0.05%-0.50%.
[0023] The catalyst for dehydrogenation of low-carbon alkane to olefins provided by this invention comprises, based on the support, 0.1–2.0% by mass, preferably 0.2%–1.0% by mass, a Group VIII metal, 0.1–2.0% by mass, a second metal component, 0.5–5.0% by mass, a Group IA metal, and 0.3–10.0% by mass, preferably 0.5–2.0% by mass, a halogen. The Group VIII metal is preferably platinum, the second metal component is preferably tin, the Group IA metal is preferably potassium, and the halogen is preferably chlorine. Preferably, based on the support, the mass percentage of platinum is 0.2%–0.5%, the mass percentage of tin is 0.1%–0.5%, the mass percentage of potassium is 0.8%–1.5%, and the mass percentage of chlorine is 1.0%–1.5%.
[0024] The low-carbon alkane dehydrogenation to olefin catalyst provided by this invention employs a millimeter-sized sulfur-containing θ-alumina microsphere, which differs from existing technologies. Preferably, these alumina microspheres have a particle size of 1.7-2.3 mm and a specific surface area of 90-130 m². 2 The particle size distribution is as follows: pore volume 0.45-0.65 mL / g, crushing strength 55-90 N / particle, bulk density 0.55-0.80 g / mL, aspect ratio b / l 0.960-0.970, sulfur content 0.15%-0.25%; more preferably, the particle size is 1.8-1.9 mm, and the specific surface area is 100-120 m² / g. 2 The particle size distribution is as follows: pore volume 0.48-0.55 mL / g, crushing strength 70-88 N / particle, bulk density 0.57-0.72 g / mL, aspect ratio b / l value 0.962-0.968, sulfur content 0.16%-0.22%. The b / l value can be used as an indicator of the aspect ratio of the particles; the closer the value is to 1, the closer the particles are to standard spheres.
[0025] The millimeter-sized sulfur-containing θ-alumina microspheres may also contain a second metal.
[0026] In the low-carbon alkane dehydrogenation to olefin catalyst provided by the present invention, the millimeter-sized sulfur-containing θ-alumina microspheres are obtained by the following steps: adding a hydrated alumina suspension to an acid solution to obtain an alumina sol, then dropping it into an oil-ammonia column through a dropper to form microspheres, drying, and calcining.
[0027] To obtain millimeter-sized sulfur-containing θ-alumina microspheres with unique physicochemical characterization parameters different from existing technologies, the hydrated alumina comprises at least two types of hydrated alumina, and at least one of the hydrated alumina is hydrated alumina P2. The hydrated alumina P2 has an acid solubility index (DI) of 50%-85%, preferably 60%-75%, and a specific surface area of 220-350 m² / g. 2 It has a pore volume of 0.3-0.7 mL / g, a sulfur content of 0.001%-0.2%, and is characterized by a high acid colloid index.
[0028] Furthermore, one of the at least two grades of hydrated alumina is hydrated alumina P2 as described above. The hydrated alumina contains 30-70% by mass, based on alumina dry basis. The other grade can be other grades of hydrated alumina, such as SB powder. In one specific embodiment of the invention, the hydrated alumina used for colloidal bonding is P2 and SB powder (from Sasol GmbH, Germany, with a specific surface area of 250 m²). 2 / g, pore volume 0.5mL / g, sulfur-free, alumina dry basis weight 50g, acid solubility index 90%).
[0029] Furthermore, to obtain better millimeter-sized sulfur-containing θ-alumina microspheres, based on the above-mentioned preparation of millimeter-sized sulfur-containing θ-alumina microspheres, in another preferred embodiment of the present invention, in addition to hydrated alumina P2 which has a high acid solubility index, the hydrated alumina also contains at least one hydrated alumina P1, that is, the hydrated alumina is a mixture of hydrated alumina P1 and hydrated alumina P2. Hydrated alumina P1 has a high pore volume, an acid solubility index (DI) of 5%-25%, and a specific surface area of 150-250 m². 2 / g, pore volume of 0.9-1.3mL / g, sulfur content of 0.001%-0.5%. The hydrated alumina P1 and the hydrated alumina P2 have a mass ratio of 0-5:1 on a dry basis, preferably 0.1-2:1.
[0030] Hydrated alumina, including the aforementioned hydrated alumina P1, can be prepared using the aluminum sulfate-sodium aluminate method, the CO2-sodium aluminate method, or the alkoxyaluminum hydrolysis method. Preferably, the aluminum sulfate-sodium aluminate method is used to prepare hydrated alumina.
[0031] The hydrated alumina P1 is obtained by neutralizing and gelling aluminum sulfate solution and sodium aluminate solution in a co-current flow, followed by aging, filtration, washing, and drying. The mass ratio of aluminum sulfate solution to sodium aluminate solution (based on Al2O3) is 0.2–1, preferably 0.3–0.8. The concentration of Al2O3 in the aluminum sulfate solution is 20–120 g / L, preferably 40–100 g / L; the concentration of Al2O3 in the sodium aluminate solution is 100–250 g / L, preferably 120–200 g / L. The neutralization and gelling temperature is 40–100℃, preferably 50–95℃. The aging temperature is 60–120℃, preferably 80–100℃, for 2–10 hours. The pH values of the system before and after neutralization and gelling are 5–10 and 8–12, respectively. Before neutralization and gelation, the pH of the system is adjusted to 5-10, preferably 6-8, using a 5-20% by mass sodium aluminate solution; after neutralization and gelation, the pH of the system is adjusted to 8-12, preferably 9-11, using a 5-20% by mass sodium aluminate solution.
[0032] The hydrated alumina P2 is obtained by mixing aluminum sulfate solution and sodium aluminate solution, neutralizing to form a gel, aging, undergoing secondary aging, and then filtering, washing, and drying. The mass ratio of aluminum sulfate solution to sodium aluminate solution (based on Al2O3) is 0.2–1, preferably 0.3–0.8. The concentration of Al2O3 in the aluminum sulfate solution is 20–120 g / L, preferably 40–100 g / L; the concentration of Al2O3 in the sodium aluminate solution is 100–250 g / L, preferably 120–200 g / L. The neutralization… The gelation process is carried out at a temperature of 40-100℃, preferably 50-95℃; the aging process is carried out at a temperature of 60-120℃, preferably 80-100℃, for 2-10 hours; the secondary aging process is carried out at a pressure of 0.1MPa to 1.0MPa, a temperature of 60-200℃, for 0.5-20 hours, preferably at a pressure of 0.2MPa to 1.0MPa, a temperature of 100-190℃, for 1-15 hours; the pH values of the system before and after gelation are 5-10 and 8-12, respectively. Before neutralization and gelation, the pH of the system is adjusted to 5-10, preferably 6-8, using a 5-20% by mass sodium aluminate solution; after neutralization and gelation, the pH of the system is adjusted to 8-12, preferably 9-11, using a 5-20% by mass sodium aluminate solution; more preferably, the pH of the system is adjusted to 9-11 after neutralization and gelation using a 10-30% by mass sodium carbonate solution.
[0033] In the above-mentioned process of preparing hydrated alumina P1 and P2, the drying temperature is 60-150℃, preferably 80-120℃.
[0034] In this invention, the millimeter-sized sulfur-containing θ-alumina microspheres used as the carrier are obtained by forming microspheres in an oil-ammonia column after acid solubilization using at least two types of hydrated alumina with different acid solubility indices (DI). The acid solubility index (DI) refers to the percentage of hydrated alumina dissolved in nitric acid solution at a specific acid-aluminum ratio within a certain reaction time, expressed as Al2O3.
[0035] The acid solubility index DI = (1-W2 / W1)×100%, where W1 and W2 are the weights of hydrated alumina before and after the reaction with acid, respectively, calculated as Al2O3.
[0036] The determination of the acid-colloidal solubility index (DI) includes:
[0037] (1) To determine the calcined basis (also known as the dry basis) of hydrated alumina, a certain amount of hydrated alumina is calcined at 800℃ for 1 hour, and the ratio of its weight after calcination to its weight before calcination is denoted as a.
[0038] (2) Weigh out W0 grams of hydrated aluminum oxide, the amount of W0 satisfies that W1, calculated as Al2O3, is 6 grams (W1 / a=W0), weigh out W grams of deionized water, W=40.0-W0, and add the weighed hydrated aluminum oxide and deionized water into a beaker and mix while stirring;
[0039] (3) Use a 20 mL pipette to transfer a 0.19 N dilute nitric acid solution and add it to the beaker in step (2). Stir and react for 8 minutes.
[0040] (4) Centrifuge the slurry after the reaction in step (3) in a centrifuge, place the precipitate into a weighed crucible, dry it at 120°C for 4 hours, calcine it at 800°C in a muffle furnace for 1 hour, and weigh it to obtain the amount of calcined sample W2g.
[0041] (5) The acid solubility index is calculated according to the formula DI=(1-W2 / W1)×100%.
[0042] The present invention provides a method for preparing millimeter-sized sulfur-containing θ-alumina microspheres as a carrier. A sol is prepared by adding an acid solution to a hydrated alumina suspension. This sol is then dropped into the oil phase of an oil-ammonia column using a dropper. The droplets shrink into spherical particles due to surface tension. These spherical particles are formed as they fall through the oil phase and undergo gelation and solidification in the ammonia-water phase. After drying and calcination, the final product is obtained. The hydrated alumina suspension has a solid content of 10–30% by mass, preferably 14–25% by mass, based on alumina. The acid is acrylic acid, tartaric acid, lactic acid, citric acid, gluconic acid, formic acid, acetic acid, nitric acid, or hydrochloric acid, preferably nitric acid or hydrochloric acid. The mass fraction of the acid in the acid solution can be 15–25% by mass. In the step of adding the hydrated alumina suspension to the acid solution to obtain the alumina sol, the mass ratio of the acid in the acid solution to the alumina contained in the hydrated alumina suspension is preferably 1.5–15%, more preferably 2–10%. The oil-ammonia column comprises an oil layer and an ammonia-water layer, wherein the oil phase in the oil layer is selected from C7-C. 16 At least one of the alkanes, preferably a single-component alkanes; the ammonia water layer has a mass fraction of 4-15% by mass, preferably 6-10% by mass; the oil layer has a thickness of 2-20 cm, preferably 4-15 cm; the ammonia water layer has a thickness of 50-300 cm, preferably 100-200 cm. The drying temperature is 60-150℃, preferably 100-120℃, and the time is 0.5-24 hours, preferably 6-12 hours; the calcination temperature is 800-1200℃, preferably 900-1100℃, and the calcination time is 0.5-24 hours, preferably 2-8 hours.
[0043] The low-carbon alkane dehydrogenation catalyst provided by this invention may have its second metal component introduced during or after the support is formed.
[0044] The low-carbon alkane dehydrogenation catalyst provided by this invention introduces the second metal component during the support molding process. This second metal precursor can be added during the preparation of millimeter-sized sulfur-containing θ-alumina microspheres to obtain millimeter-sized sulfur-containing θ-alumina microspheres containing the second metal. First, the millimeter-sized sulfur-containing θ-alumina microspheres containing the second metal are impregnated with a mixed impregnation solution containing a Group VIII metal compound and a halogen-containing compound. The impregnated solid is then dried, calcined, and then impregnated again with a solution containing a Group IA metal compound, dried, calcined, and reduced. The precursor containing the second metal is selected from compounds that can form soluble or dispersible sols, such as their chlorides, oxides, hydroxides, or oxychlorides. If the second metal is tin, the tin precursor can be stannous chloride or stannous tetrachloride. The Group VIII metal compound is chloroplatinic acid or ammonium chloroplatinate. The halogen-containing compound is preferably hydrogen chloride or a chlorinated organic acid, such as dichloroacetic acid or trichloroacetic acid. The halogen compound contained in the mixed impregnation solution accounts for 1.1 to 2.8% of the mass of the carrier, and the liquid / solid ratio during impregnation is 1.3 to 3.0 ml / g. The water-soluble compound containing Group IA metals is potassium hydroxide, potassium nitrate, or potassium chloride. The impregnation, drying, calcination, and reduction processes described in this application are conventional operations in the art and will not be elaborated further here.
[0045] The low-carbon alkane dehydrogenation catalyst provided by this invention introduces the second metal component after the support is formed using an impregnation method. This can be achieved by using millimeter-sized sulfur-containing θ-alumina microspheres as the support, first impregnating them with a mixed impregnation solution containing a Group VIII metal compound, a precursor of the second metal, and a halogen-containing compound. The impregnated solid is then dried, calcined, and then impregnated again with a solution containing a Group IA metal compound, followed by drying, calcination, and reduction. Alternatively, the same method can be used: first impregnating the aforementioned millimeter-sized sulfur-containing θ-alumina microspheres with an impregnation solution containing a precursor of the second metal, then drying and calcining the impregnated solid, followed by impregnation again with a mixed impregnation solution containing a Group VIII metal compound and a halogen-containing compound, then drying, calcining, and finally impregnating again with a solution containing a Group IA metal compound, followed by drying, calcination, and reduction. The precursor containing the second metal is selected from compounds capable of forming soluble or dispersible sols, such as their chlorides, oxides, hydroxides, or oxychlorides. If the second metal is tin, the tin precursor can be stannous chloride or stannous tetrachloride. The compound containing Group VIII metals is chloroplatinic acid or ammonium chloroplatinate. The halogen-containing compound is preferably hydrogen chloride or a chlorinated organic acid, such as dichloroacetic acid or trichloroacetic acid. The mass of the halogen compound in the mixed impregnation solution is 1.1–2.8% of the mass of the carrier, and the liquid / solid ratio during impregnation is 1.3–3.0 ml / g. The water-soluble compound containing Group IA metals is potassium hydroxide, potassium nitrate, or potassium chloride. The impregnation, drying, calcination, and reduction processes described in this application are conventional operations in the art and will not be elaborated further here.
[0046] The catalyst provided by this invention is suitable for the dehydrogenation of low-carbon alkanes to olefins. Because the catalyst contains a certain amount of sulfur, the pre-sulfurization step can be omitted before the reaction. The low-carbon alkane is propane, butane, or pentane, and the butane is n-butane or isobutane. Propane is the preferred low-carbon alkane for the reaction. The reaction is carried out in the presence of hydrogen with the low-carbon alkane and the alkane dehydrogenation catalyst provided by this invention at 400–800°C, preferably 550–650°C, and a pressure of 0.1–1.0 MPa, preferably 0.1–0.5 MPa. During the reaction, the suitable mass hourly space velocity (HHSV) for contact between the low-carbon alkane and the catalyst is 0.1–20 h⁻¹. -1 More preferably 0.5 to 10 h -1 The molar ratio of hydrogen to low-carbon alkanes is preferably 0.1–10:1, more preferably 0.3–3:1. Alternatively, water vapor, argon, methane, ethane, carbon dioxide, nitrogen, etc., can be used as diluents to mix with the low-carbon alkanes and hydrogen before being introduced into the reactor.
[0047] The present invention will be further illustrated by the following examples, but these examples do not limit the scope of the invention.
[0048] In the examples and comparative examples,
[0049] The crushing strength of alumina pellets was measured using a ZQJ intelligent particle strength tester manufactured by Dalian Equipment Diagnostic Instrument Factory, with a force application rate of 5 N / s and a range of 250 N.
[0050] The specific surface area and pore volume of alumina microspheres were determined by low-temperature nitrogen adsorption method. The specific surface area was calculated by BET method, and the pore volume was calculated when the relative pressure P / P0 was 0.99. P is the measurement pressure, and P0 is the saturated vapor pressure of N2 at the adsorption temperature.
[0051] The particle size and aspect ratio b / l of the alumina microspheres were measured using the dynamic digital imaging principle of the German CAMSIZER multi-functional particle size and shape analyzer.
[0052] The sulfur content of the alumina pellets was determined by a high-frequency combustion infrared absorption sulfur carbon analyzer, specifically the CS-344 infrared sulfur carbon analyzer manufactured by LECO Corporation, USA.
[0053] Example 1
[0054] (1) Preparation of hydrated alumina P1:
[0055] Add 200 mL of deionized water to a gelling tank and heat to 60 °C. While stirring thoroughly, simultaneously add 200 mL of aluminum sulfate solution (concentration of 50 g / L based on alumina) and 140 mL of sodium aluminate solution (concentration of 150 g / L based on alumina). The mass ratio of aluminum sulfate solution to sodium aluminate solution (based on Al2O3) is 0.48. Adjust the pH of the reactants to 7.5 with 12% sodium aluminate solution and neutralize for 60 minutes. Then, adjust the pH of the system to 9.5 with 12% sodium aluminate solution, raise the temperature to 90 °C, and continue stirring and aging for 4 hours. Filter the mixture; the main component of the filter cake is hydrated alumina. Wash and filter the filter cake three times with deionized water at 30 °C, using 500 mL of water each time for 30 minutes. The filter cake obtained from the final washing was dried at 120°C for 12 hours to obtain hydrated alumina powder P1.
[0056] The specific surface area of P1 is 180 m². 2 / g, pore volume is 1.0mL / g, most probable pore size is 25nm, sulfur content is 0.35%, and acid solubility index (DI) is 18%.
[0057] (2) Preparation of hydrated alumina P2:
[0058] Add 200 mL of deionized water to a gelling tank and heat to 60 °C. While stirring thoroughly, simultaneously add 210 mL of aluminum sulfate solution (concentration of 50 g / L based on alumina) and 130 mL of sodium aluminate solution (concentration of 150 g / L based on alumina) to the gelling tank. The mass ratio of aluminum sulfate solution to sodium aluminate solution (based on Al2O3) is 0.54. Adjust the pH of the reactants to 7.5 with 12% sodium aluminate solution and neutralize for 60 minutes. Then, adjust the pH of the system to 9.5 with 20% sodium carbonate solution, raise the temperature to 90 °C, and continue stirring for aging for 4 hours. Transfer the aged mixture to an autoclave, pressurize to 0.4 MPa, and heat to 160 °C in an oven for a second aging of 12 hours. Filter the mixture; the main component of the filter cake is hydrated alumina. The filter cake was subjected to three slurry washings and filtrations with deionized water at 30°C, with 500 mL of water used each time for 30 minutes. The filter cake obtained from the last washing was dried at 120°C for 12 hours to obtain hydrated alumina powder P2.
[0059] The specific surface area of P2 is 250 m². 2 The pore volume is 0.6 mL / g, the most probable pore size is 9.0 nm, the sulfur content is 0.15%, and the acid solubility index (DI) is 65%, indicating that it has a high acid solubility index.
[0060] (3) Oil-ammonia column molding:
[0061] The oil layer of the oil-ammonia column is composed of C9 alkane with a thickness of 5 cm, while the ammonia layer has a thickness of 150 cm and an ammonia concentration of 6% by mass.
[0062] Take 64g (1) of P1 powder (alumina dry basis mass is 50g) and 62.5g (2) of P2 powder (alumina dry basis mass is 50g) and mix with 370g of deionized water for 30 minutes. The solid content of the alumina suspension based on alumina dry basis is 20.1% by mass. The mass ratio of P1 to P2 is 1:1. Add 20g of 20% by mass nitric acid solution dropwise and gelatinize for 60 minutes to prepare alumina sol. The acid solution is 4% by mass of the alumina dry basis contained in the hydrated alumina suspension. Then, add the alumina sol dropwise into an oil-ammonia column. After the alumina sol droplets form spheres in the oil layer, they pass through the oil-water interface and are solidified in the ammonia water layer for 1 hour. The alumina wet spheres are obtained. The alumina wet spheres are dried at 110℃ for 4 hours and calcined at 950℃ for 4 hours to obtain alumina microsphere samples, which are numbered Q1.
[0063] The physical properties, crushing strength, aspect ratio and sulfur content of Q1 are shown in Table 1.
[0064] (4) Preparation of alkane dehydrogenation catalyst
[0065] Take the above-mentioned θ-Al₂O₃ microspheres Q1, first impregnate them with a hydrochloric acid solution containing stannous chloride at 25°C for 4 hours. The impregnation solution contains 0.32% by mass of tin (relative to dry alumina), and the liquid / solid ratio is 1.8 mL / g. The resulting solid is dried at 120°C for 12 hours and calcined at 500°C for 4 hours to obtain a tin-containing θ-Al₂O₃ support. Then, impregnate it with a mixed impregnation solution containing chloroplatinic acid and hydrochloric acid at 25°C for 4 hours. The mixed impregnation solution contains 0.30% by mass of platinum and 2.0% by mass of chlorine (both relative to dry alumina), and the liquid / solid ratio is 1.8 mL / g. The resulting solid is dried at 120°C for 12 hours and calcined at 500°C for 4 hours. The calcined solid is then impregnated with a potassium nitrate solution at 25°C for 4 hours. The potassium nitrate solution contains 1.0% by mass of potassium (relative to dry alumina), and the liquid / solid ratio is 1.4 mL / g. The solid obtained after impregnation was dried at 120°C for 12 hours and calcined at 600°C for 4 hours. The calcined catalyst was then reduced with hydrogen at 550°C for 2 hours to obtain catalyst C1.
[0066] The catalyst C1 contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.25% by mass Cl, and 0.15% by mass sulfur.
[0067] Example 2
[0068] Hydrated alumina P1 powder and P2 powder were prepared sequentially according to the methods in Example 1 (1) and (2).
[0069] (3) Oil-ammonia column molding:
[0070] The oil layer of the oil-ammonia column is composed of C9 alkane with a thickness of 5 cm, while the ammonia layer has a thickness of 150 cm and an ammonia concentration of 6% by mass.
[0071] Take 77g of (1) P1 powder (60g dry alumina), 50.0g of (2) P2 powder (40g dry alumina), and 350g of deionized water and mix for 30 minutes. The solid content of the alumina suspension based on dry alumina is 21.0% by mass, and the mass ratio of P1 to P2 is 6:4. Add 30g of 20% by mass hydrochloric acid solution dropwise and gelatinize for 60 minutes to prepare alumina sol. The acid solution is 6% by mass of the dry alumina contained in the hydrated alumina suspension. Then, add the alumina sol dropwise to the same oil-ammonia column as in Example 1. After the alumina sol droplets form spheres in the oil layer, they pass through the oil-water interface and are solidified in the ammonia water layer for 1 hour. The alumina wet spheres are obtained. The alumina wet spheres are dried at 110℃ for 4 hours and calcined at 1000℃ for 4 hours to obtain alumina microsphere samples, which are numbered Q2.
[0072] The physical properties, crushing strength, aspect ratio and sulfur content of Q2 are shown in Table 1.
[0073] (4) Preparation of alkane dehydrogenation catalyst
[0074] An alkane dehydrogenation catalyst was prepared in accordance with Example 1(4) to obtain catalyst C2.
[0075] The catalyst C2 contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.21% by mass Cl, and 0.13% by mass sulfur.
[0076] Example 3
[0077] Hydrated alumina P1 powder and P2 powder were prepared sequentially according to the methods in Example 1 (1) and (2).
[0078] (3) Oil-ammonia column molding:
[0079] The oil layer of the oil-ammonia column is composed of C9 alkane with a thickness of 5 cm, while the ammonia layer has a thickness of 150 cm and an ammonia concentration of 6% by mass.
[0080] Take 51g (1) of P1 powder (alumina dry basis mass is 40g), 75g (2) of P2 powder (alumina dry basis mass is 60g), and 360g of deionized water and mix for 30 minutes. The solid content of the alumina suspension based on alumina dry basis is 20.6% by mass, and the mass ratio of P1 to P2 is 4:6. Add 15g of 20% by mass nitric acid solution dropwise and gelatinize for 60 minutes to prepare alumina sol. The acid solution is 3% by mass of the alumina dry basis contained in the hydrated alumina suspension. Then, add the alumina sol dropwise to the same oil-ammonia column as in Example 1. After the alumina sol droplets form spheres in the oil layer, they pass through the oil-water interface and are solidified in the ammonia water layer for 1 hour. The alumina wet spheres are obtained. The alumina wet spheres are dried at 110℃ for 4 hours and calcined at 1050℃ for 4 hours to obtain alumina microsphere samples, numbered Q4.
[0081] The physical properties, crushing strength, aspect ratio and sulfur content of Q3 are shown in Table 1.
[0082] An alkane dehydrogenation catalyst was prepared in accordance with Example 1(4) to obtain catalyst C3.
[0083] The catalyst C3 contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.22% by mass Cl, and 0.14% by mass sulfur.
[0084] Example 4
[0085] Hydrated alumina P2 powder was prepared in accordance with Example 1(2).
[0086] (3) Oil-ammonia column molding:
[0087] The oil layer of the oil-ammonia column is composed of C9 alkane with a thickness of 5 cm, while the ammonia layer has a thickness of 150 cm and an ammonia concentration of 6% by mass.
[0088] Take 62.5g (2) of P2 powder (alumina dry basis mass is 50g), 66.7g of SB powder (Sasol, Germany, specific surface area 250m²) 2Alumina sol (containing 50 g of alumina dry basis and a pore volume of 0.5 mL / g, sulfur-free, with a dry basis mass of 50 g and a gelation index of 90%) was mixed with 360 g of deionized water and stirred for 30 minutes. The solid content of the alumina suspension, based on the dry basis of alumina, was 20.4% by mass. The P2:SB mass ratio was 5:5. 13 g of 20% by mass nitric acid solution was added dropwise and the gelation reaction was carried out for 60 minutes to prepare alumina sol. The acid solution contained 2.6% by mass of the dry basis of alumina in the hydrated alumina suspension. Then, the alumina sol was added dropwise to the same oil-ammonia column as in Example 1. After the alumina sol droplets formed into spheres in the oil layer, they passed through the oil-water interface and were cured in the ammonia water layer for 1 hour. The alumina wet spheres were then obtained. The alumina wet spheres were dried at 110 °C for 4 hours and calcined at 1050 °C for 4 hours to obtain alumina microsphere samples, numbered Q4.
[0089] The physical properties, crushing strength, aspect ratio, and sulfur content of Q4 are shown in Table 1.
[0090] An alkane dehydrogenation catalyst was prepared in accordance with Example 1(4) to obtain catalyst C4.
[0091] The catalyst C4 contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.18% by mass Cl, and 0.08% by mass sulfur.
[0092] Example 5
[0093] Alumina microspheres Q5 were prepared according to the methods in Examples 1(1), (2), and (3), except that the amounts of aluminum sulfate and sodium aluminate used in the preparation of hydrated alumina P2 were 180 ml and 120 ml, respectively; the specific surface area of the resulting P2 was 264 m². 2 / g, pore volume is 0.63mL / g, most probable pore size is 9.7nm, sulfur content is 0.16%, acid solubility index (DI) is 69%; the physical properties, crushing strength, aspect ratio and sulfur content of the obtained Q5 are shown in Table 1.
[0094] An alkane dehydrogenation catalyst was prepared in accordance with Example 1(4) to obtain catalyst C5.
[0095] Catalyst C5 contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.20% by mass Cl, and 0.14% by mass sulfur.
[0096] Example 6
[0097] Alumina microspheres Q6 were prepared according to the methods in Examples 1(1), (2), and (3). The difference was that the secondary aging conditions for preparing hydrated alumina P2 were: pressure 0.5 MPa, pH 10, temperature 180℃, and time 6 hours; the specific surface area of the resulting P2 was 270 m². 2 / g, pore volume is 0.56mL / g, most probable pore size is 9.4nm, sulfur content is 0.16%, acid solubility index (DI) is 70%; the physical properties, crushing strength, aspect ratio and sulfur content of the obtained Q6 are shown in Table 1.
[0098] An alkane dehydrogenation catalyst was prepared in accordance with Example 1(4) to obtain catalyst C6.
[0099] The C6 catalyst contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.22% by mass Cl, and 0.14% by mass sulfur.
[0100] Example 7
[0101] Alumina microspheres Q7 were prepared according to the methods in Examples 1(1), (2), and (3), except that the amounts of aluminum sulfate and sodium aluminate used in the preparation of hydrated alumina P1 were 160 ml and 120 ml, respectively; the specific surface area of the resulting P1 was 190 m². 2 / g, pore volume is 1.05mL / g, most probable pore size is 23.6nm, sulfur content is 0.30%, acid solubility index (DI) is 20%; the physical properties, crushing strength, aspect ratio and sulfur content of the obtained Q7 are shown in Table 1.
[0102] An alkane dehydrogenation catalyst was prepared in accordance with Example 1(4) to obtain catalyst C7.
[0103] The catalyst C7 contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.24% by mass Cl, and 0.14% by mass sulfur.
[0104] Example 8
[0105] Alumina microspheres Q8 were prepared according to the methods in Examples 1(1), (2), and (3), except that in the oil-ammonia column forming step, stannous chloride was added to the alumina sol so that the Sn content in the solution was 0.32% of the dry alumina mass. The resulting Q8 had a tin content of 0.32% by mass based on the total mass of the alumina microspheres. The physical properties, crushing strength, aspect ratio, and sulfur content of Q8 are shown in Table 1.
[0106] The alkane dehydrogenation catalyst was prepared according to Example 1(4), except that the step of impregnating alumina pellets with stannous chloride solution was omitted, and catalyst C8 was obtained.
[0107] The C8 catalyst contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.16% by mass Cl, and 0.15% by mass sulfur.
[0108] Example 9
[0109] Alumina microspheres Q9 were prepared according to the methods in Examples 1(1), (2), and (3). The difference was that when preparing hydrated alumina P2, the pH of the system was adjusted to 9.5 with a 12% by mass sodium aluminate solution after neutralization and gelation; the specific surface area of the resulting P2 was 230 m². 2 / g, pore volume is 0.5mL / g, most probable pore size is 9.2nm, sulfur content is 0.16%, acid solubility index (DI) is 53%; the physical properties, crushing strength, aspect ratio and sulfur content of the obtained Q9 are shown in Table 1.
[0110] An alkane dehydrogenation catalyst was prepared in the manner described in Example 1(4) to obtain catalyst C9.
[0111] The catalyst C9 contains 0.3% by mass platinum, 0.2% by mass tin, 1.0% by mass potassium, 1.25% by mass Cl, and 0.16% by mass sulfur.
[0112] Example 10
[0113] Hydrated alumina P1 and P2 powders were prepared sequentially according to the methods in Examples 1(1) and (2).
[0114] Alumina microspheres Q10 were prepared in accordance with the method of Example 2(3), except that stannous chloride was added to the alumina sol so that the Sn content in the sol was 0.32% of the dry alumina mass. The resulting Q10 had a tin content of 0.32% by mass based on the total mass of the alumina microspheres. Its physical properties, crushing strength, aspect ratio and sulfur content are shown in Table 1.
[0115] The alkane dehydrogenation catalyst C10 was prepared according to the method in Example 1(4), except that the step of impregnating alumina pellets with stannous chloride solution was omitted.
[0116] The C10 catalyst contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.20% by mass Cl, and 0.15% by mass sulfur.
[0117] Example 11
[0118] Hydrated alumina P1 and P2 powders were prepared sequentially according to the methods in Examples 1(1) and (2).
[0119] Alumina microspheres Q11 were prepared in accordance with the method of Example 3(3), except that stannous chloride was added to the alumina sol so that the Sn content in the sol was 0.32% of the dry alumina mass. The resulting Q10 had a tin content of 0.32% by mass based on the total mass of the alumina microspheres. Its physical properties, crushing strength, aspect ratio and sulfur content are shown in Table 1.
[0120] The alkane dehydrogenation catalyst C11 was prepared according to the method in Example 1(4), except that the step of impregnating alumina pellets with stannous chloride solution was omitted.
[0121] The catalyst C11 contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.18% by mass Cl, and 0.13% by mass sulfur.
[0122] Example 12
[0123] Hydrated alumina P2 powder was prepared sequentially according to the method of Example 1(2).
[0124] Alumina microspheres Q12 were prepared in the manner described in Example 4(3), except that stannous chloride was added to the alumina sol so that the Sn content in the sol was 0.32% of the dry alumina mass. The resulting Q12 had a tin content of 0.32% by mass based on the total mass of the alumina microspheres. Its physical properties, crushing strength, aspect ratio and sulfur content are shown in Table 1.
[0125] The alkane dehydrogenation catalyst C12 was prepared according to the method in Example 1(4), except that the step of impregnating alumina pellets with stannous chloride solution was omitted.
[0126] The catalyst C12 contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.22% by mass Cl, and 0.10% by mass sulfur.
[0127] Example 13
[0128] Catalyst C13 was prepared in the manner described in Example 1, except that (4) the step of impregnating with stannous chloride solution was omitted, and the mixed impregnation solution contained 0.32% by mass of tin, 0.30% by mass of platinum, and 2.0% by mass of chlorine relative to dry alumina.
[0129] The catalyst C13 contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.23% by mass Cl, and 0.14% by mass sulfur.
[0130] Example 14
[0131] Catalyst C14 was prepared in the manner described in Example 8, except that (4) the mixed impregnation solution contained 0.35% by mass of platinum and 1.6% by mass of chlorine (both relative to dry alumina).
[0132] The catalyst C14 contains 0.35% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.14% by mass Cl, and 0.15% by mass sulfur.
[0133] Comparative Example 1
[0134] This comparative example illustrates the preparation of alumina sol using only the P1 comparative catalyst during the support preparation.
[0135] Hydrated alumina P1 powder was prepared according to step 1 of Example 1 (1).
[0136] Take 130g of P1 powder obtained in step (1) (alumina dry basis mass is 100g) and mix it with 360g of deionized water and stir for 30 minutes. Add 40g of 20% nitric acid solution dropwise and gelatinize for 60 minutes to prepare alumina sol. The acid solution is 8% of the alumina dry basis contained in the hydrated alumina suspension. Then, add the alumina sol dropwise into the same oil-ammonia column as in Example 1. After the alumina sol droplets form spheres in the oil layer, they pass through the oil-water interface and are solidified in the ammonia water layer for 1 hour. The alumina wet spheres are then obtained. The alumina wet spheres are dried at 110℃ for 4 hours and calcined at 1000℃ for 4 hours to obtain alumina microspheres. The comparative sample is numbered DQ1.
[0137] The physical properties, crushing strength, aspect ratio, and sulfur content of DQ1 are shown in Table 1.
[0138] An alkane dehydrogenation catalyst was prepared in accordance with the method of Example 1(4) to obtain comparative catalyst D1.
[0139] In contrast, catalyst D1 contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.22% by mass Cl, and 0.14% by mass sulfur.
[0140] Comparative Example 2
[0141] This comparative example illustrates the preparation of alumina sol using only P2 as a comparative catalyst during the support preparation.
[0142] Hydrated alumina P2 powder was prepared according to step 1(2) of Example.
[0143] Take 125g of P2 powder obtained in step (1) (alumina dry basis mass is 100g) and mix it with 360g of deionized water and stir for 30 minutes. Add 15g of nitric acid solution with a concentration of 20% by mass dropwise and gelatinize for 60 minutes to prepare alumina sol. The acid solution is 3% by mass of the alumina dry basis contained in the hydrated alumina suspension. Then, add the alumina sol dropwise into the same oil-ammonia column as in Example 1. After the alumina sol droplets form spheres in the oil layer, they pass through the oil-water interface and are solidified in the ammonia water layer for 1 hour. The alumina wet spheres are then obtained. The alumina wet spheres are dried at 110℃ for 4 hours and calcined at 1000℃ for 4 hours to obtain alumina microspheres. The comparative sample is numbered DQ2.
[0144] The physical properties, crushing strength, aspect ratio, and sulfur content of DQ2 are shown in Table 1.
[0145] The alkane dehydrogenation catalyst was prepared according to Example 1(4), and comparative catalyst D2 was obtained.
[0146] In contrast, catalyst D2 contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.20% by mass Cl, and 0.13% by mass sulfur.
[0147] Comparative Example 3
[0148] This comparative example illustrates the preparation of a comparative catalyst using only conventional SB powder in the alumina sol support preparation.
[0149] Take 133g of SB powder (Sasol, Germany, specific surface area 250m²). 2 Alumina sol (containing 100g of alumina dry basis and a pore volume of 0.5mL / g, sulfur-free, with a dry basis mass of 100g and a gelation index of 90%) was mixed with 350g of deionized water and stirred for 30 minutes. Then, 15g of 20% nitric acid solution was added dropwise for 30 minutes to prepare alumina sol. The acid solution was 3% of the dry basis of alumina contained in the hydrated alumina suspension. The alumina sol was then added dropwise to the same oil-ammonia column as in Example 1. After the alumina sol droplets formed into spheres in the oil layer, they passed through the oil-water interface and were cured in the ammonia water layer for 1 hour to obtain alumina wet spheres. The alumina wet spheres were dried at 110℃ for 4 hours and calcined at 1000℃ for 4 hours to obtain alumina microspheres as a comparative sample, numbered DQ3.
[0150] The physical properties, crushing strength, aspect ratio, and sulfur content of DQ3 are shown in Table 1.
[0151] The alkane dehydrogenation catalyst was prepared according to Example 1(4), and comparative catalyst D3 was obtained.
[0152] In contrast, catalyst D3 contains 0.3% by mass platinum, 0.32% by mass tin, 1.0% by mass potassium, 1.20% by mass Cl, and 0% by mass sulfur.
[0153] Table 1
[0154]
[0155] Example 15-28
[0156] Examples 15-28 illustrate the application of the catalyst of the present invention in the propane dehydrogenation reaction.
[0157] In a microreactor, 3 mL of catalyst C1 was loaded, using a mixture of propane and hydrogen as feedstock, and the reaction was carried out at 620 °C, 0.10 MPa, and a propane feed mass hourly space velocity of 3.6 h⁻¹. -1The reaction was carried out for 10 hours under the condition that the molar ratio of hydrogen to propane was 0.4:1. Samples were taken every 1.0 hour for chromatographic analysis, and the propane conversion rate and propylene selectivity were calculated. The results are shown in Table 2.
[0158] The C2-C14 catalysts were used for propane dehydrogenation as described above, and the results are shown in Table 2.
[0159] Comparative Examples 4-6
[0160] Comparative Examples 4-6 illustrate the use of comparative catalysts DC1, DC2, and DC3 in the propane dehydrogenation reaction.
[0161] The reaction conditions are the same as in Example 15.
[0162] The results are shown in Table 2.
[0163] Table 2
[0164]
[0165] As shown in Table 2, the catalyst of the present invention has a higher propane conversion rate, higher propylene selectivity, better catalyst activity stability, and lower coking after reaction compared with the comparative catalyst.
Claims
1. A catalyst for dehydrogenation of a lower alkane to an alkene comprising an alumina support and an active component, characterized in that, The alumina carrier is a millimeter-sized sulfur-containing theta-alumina bead with a particle size of 1.6-2.5 mm, a specific surface area of 80-150 m 2 / g, a pore volume of 0.40-0.75 mL / g, a crushing strength of greater than 50 N / particle, a bulk density of 0.55-0.80 g / mL, an aspect ratio b / l value of 0.95 or greater, and a sulfur content of 0.05%-0.50%.
2. Catalyst according to claim 1, characterized in that The active component comprises 0.1-2.0 mass%, preferably 0.2%-1.0% mass of Group VIII metal, 0.1-2.0 mass% of the second metal component, 0.5-5.0 mass% of Group IA metal and 0.3-10.0 mass%, preferably 0.5-2.0% of halogen, based on the carrier.
3. The catalyst according to claim 1, characterized in that, The Group VIII metal is platinum, the second metal component is tin, the Group IA metal is potassium and the halogen is chlorine.
4. The catalyst according to claim 1, characterized in that, The millimeter-sized sulfur-containing θ-alumina pellet has a particle size of 1.7-2.3 mm, a specific surface area of 90-130 m 2 / g, a pore volume of 0.45-0.65 mL / g, a crushing strength of 55-90 N / pellet, a bulk density of 0.55-0.80 g / mL, a length-diameter ratio b / l value of 0.960-0.970, and a sulfur content of 0.15%-0.25%.
5. The catalyst according to claim 1, characterized in that, The millimeter-sized sulfur-containing θ-alumina pellet has a particle size of 1.8-1.9 mm, a specific surface area of 100-120 m 2 / g, a pore volume of 0.48-0.55 mL / g, a crushing strength of 70-88 N / pellet, a bulk density of 0.57-0.72 g / mL, a length-diameter ratio b / l value of 0.962-0.968, and a sulfur content of 0.16%-0.22%.
6. Catalyst according to one of claims 1 to 5, characterized in that Millimeter-sized sulfur-containing theta-alumina beads contain a second metal.
7. Catalyst according to one of claims 1 to 5, characterised in that The millimeter-sized sulfur-containing theta-alumina beads are obtained by the steps comprising adding a suspension of hydrated alumina to an acid solution to obtain an alumina sol, and then dropping the sol into an oil ammonia column through a dropping head to form beads, drying and calcining the beads, wherein the hydrated alumina comprises at least two kinds of hydrated alumina, and at least one of the hydrated alumina is hydrated alumina P2, the acid peptization index DI of which is 50%-85%, preferably 60%-75%, and the sulfur content is 0.001%-0.2%.
8. The catalyst according to claim 7, characterized in that At least one of the hydrated alumina is hydrated alumina P1, the acid peptization index DI of which is 5%-25%, and the sulfur content is 0.001%-0.5%.
9. The catalyst according to claim 8, characterized in that The hydrated alumina is a mixture of the hydrated alumina P1 and the hydrated alumina P2.
10. The catalyst according to claim 9, characterized in that The mass ratio of the hydrated alumina P1 to the hydrated alumina P2 is 0-5:1, preferably 0.1-2:1, on a dry basis.
11. The catalyst according to claim 7, characterized in that, The content of P2 in the hydrated alumina is 30-70 mass%, on an alumina dry basis.
12. The catalyst according to claim 7, characterized in that, The hydrated alumina P1 is obtained by mixing an aluminum sulfate solution and a sodium metaaluminate solution, neutralizing and peptizing, aging, filtering, washing and drying; wherein the mass ratio of the aluminum sulfate solution to the sodium metaaluminate solution, on an Al2O3 basis, is 0.2-1, preferably 0.3-0.8; the concentration of Al2O3 in the aluminum sulfate solution is 20-120 g / L, preferably 40-100 g / L; the concentration of Al2O3 in the sodium metaaluminate solution is 100-250 g / L, preferably 120-200 g / L; the neutralizing and peptizing temperature is 40-100℃, preferably 50-95℃; the aging temperature is 60-120℃, preferably 80-100℃; and the pH values of the system before and after the neutralizing and peptizing are 5-10 and 8-12, respectively.
13. The catalyst according to claim 12, characterized in that The pH value of the system before the neutralizing and peptizing is adjusted to 5-10, preferably 6-8, by using the sodium metaaluminate solution; and the pH value of the system after the neutralizing and peptizing is adjusted to 8-12, preferably 9-11, by using the sodium metaaluminate solution.
14. The catalyst according to claim 7, characterized in that, The hydrated aluminum oxide P2 is obtained by mixing aluminum sulfate solution and sodium metaaluminate solution, neutralization, gelation, aging, secondary aging, filtration, washing and drying. The mass ratio of aluminum sulfate solution and sodium metaaluminate solution based on Al2O3 is 0.2-1, preferably 0.3-0.
8. The concentration of Al2O3 in the aluminum sulfate solution is 20-120 g / L, preferably 40-100 g / L. The concentration of Al2O3 in the sodium metaaluminate solution is 100-250 g / L, preferably 120-200 g / L. The temperature of the neutralization and gelation is 40-100℃, preferably 50-95℃. The temperature of the aging is 60-120℃, preferably 80-100℃. The secondary aging is carried out at a pressure of 0.1-1.0 MPa and a temperature of 60-200℃ for 0.5-20 hours. The pH of the system before and after the neutralization and gelation is 5-10 and 8-12, respectively.
15. The catalyst according to claim 14, characterized in that The pH of the system before the neutralization and gelation is adjusted to 5-10, preferably 6-8, by sodium metaaluminate solution. The pH of the system after the neutralization and gelation is adjusted to 8-12, preferably 9-11, by sodium metaaluminate solution or sodium carbonate solution.
16. The catalyst according to claim 14, characterized in that The secondary aging is carried out at a pressure of 0.2-1.0 MPa and a temperature of 100-190℃ for 1-15 hours.
17. The catalyst according to claim 7, characterized in that, The acid in the acid solution is acrylic acid, tartaric acid, lactic acid, citric acid, gluconic acid, formic acid, acetic acid, nitric acid or hydrochloric acid, preferably nitric acid or hydrochloric acid.
18. The preparation method according to claim 7, characterized in that, The mass ratio of the acid in the acid solution to the aluminum oxide in the hydrated aluminum oxide suspension is 1.5-15%.
19. The catalyst according to claim 7, characterized in that, The solid content of the hydrated aluminum oxide suspension based on Al2O3 is 10-30 mass%.
20. The catalyst according to claim 7, characterized in that, The oil-ammonia column comprises an oil layer and an ammonia water layer, the oil phase in the oil layer is at least one selected from C7-C 16 alkanes, the mass fraction of ammonia water in the ammonia water layer is 4-15 mass%, the thickness of the oil layer is 2-20 cm, and the thickness of the ammonia water layer is 50-300 cm.
21. The catalyst according to claim 7, characterized in that, The drying is carried out at a temperature of 60-150℃, and the calcination is carried out at a temperature of 800-1200℃.
22. The catalyst of claim 7, further comprising a second metal precursor added to the alumina sol.
23. The catalyst of claim 3, wherein the mass ratio of platinum is 0.2-0.5%, the mass ratio of tin is 0.1-0.5%, the mass ratio of potassium is 0.8-1.5%, and the mass ratio of chlorine is 1.0-1.5%, based on the support.
Citation Information
Patent Citations
Vulcanization and startup method of dehydrogenation catalyst
CN102463148A
Method for processing dehydrogenation catalyst before application
CN102463152A
Method for preparing spherical alumina particles by alginic acid auxiliary forming method
CN102718241B
Activation method for dehydrogenation catalyst
CN102909012A
Preparation method of alumina pellets through hot oil column moulding
CN105502447A
